Approaches to Legal Ontologies
XIV, 282 p.
Keywords: Legal ontologies have proved crucial for representing, processing and retrieving legal information, and will acquire an increasing significance in the emerging framework of the Semantic Web. Despite the many research projects in the field, a collective reflection on the theoretical foundations of legal ontology engineering was still missing. This book bridges the gap, by exploring current methodologies and theoretical approaches to legal ontologies. It gathers 16 papers, each of them presenting issues and solutions for ontology engineering related to a particular approach to, or aspect of, the law: comparative law, case-based reasoning, multilingualism, complex- systems, sociolegal analysis, legal theory, social ontology, ontology learning, computational ontology, service ontology, cognitive science, document modelling, large legal databases, scientific, linguistic and legal-technology perspectives. The book will thus interest researchers in legal informatics, artificial intelligence and law, legal theory, legal philosophy, legal sociology, comparative law, as well as developers of applications based on the intelligent management of legal information, in both e-commerce and e-government (e-administration, e-justice, e-democracy).